FAMILY ASSISTANCE FOR STUNTING INCIDENTS IN TENGGER CHILDREN, PASURUAN DISTRICT INDONESIA - Puspitasari, RA Helda; Handayani, Dwining; Kusuma, Erik; Nastiti, Ayu Dewi; Tsai, Mei-Ling (SYNTHESIS Global Health Journal, 2024)
Backgrounds.  Stunting commonly known as short stature can be interpreted as a condition where the body is short or very short below normal for age. This community service aimed to determine the relationship between the use of clean water, healthy latrines, washing hands with soap, and the incidence of stunting in children in Tengger, Pasuruan Regency. Implementation Method. This community service uses family assistance with a planning-organizing-actuating-controlling (POAC) approach. The mothers of children in Tengger, Pasuruan, totaling 46 mothers and their children, accompanied them for two weeks. To prove that this community service is successful, the author examines the use of clean water, healthy latrines, and washing hands with soap to prevent the risk of stunting. Findings. After community service, there was a significant change in behavior in the family. Mothers are more aware of their children's health status. Children use clean water, healthy latrines, use soap to wash their hands. Conclusion. Preventing the risk of stunting is an important action to support the development of children's health status.